Patients with repaired tetralogy of Fallot and the HIF1A1744C/T variant have increased imaging markers of diffuse myocardial fibrosis. (1st March 2022) - Vaikom House, Aswathy K.; Chetan, Devin; Mital, Seema; Grosse-Wortmann, Lars
Abstract: Background: Right ventricular fibrotic remodeling has been identified pre- and postoperatively in patients with tetralogy of Fallot (ToF) and linked to adverse outcomes. Polymorphisms of hypoxia inducible factor-1-alpha ( HIF1A ) have been associated with the fibrotic burden by cardiac magnetic resonance (CMR) late gadolinium enhancement imaging. Their association with diffuse fibrotic myocardial remodeling is unknown. We sought to determine whether polymorphisms in HIF1A are related to CMR markers of diffuse myocardial fibrosis. Methods: Patients with repaired ToF who had undergone CMR with T1 mapping as well as whole genome sequencing were included. Myocardial native T1 was quantified using a modified Look-Locker inversion recovery sequence and measured in the left ventricular free wall, the interventricular septum, and the right ventricular free wall. Patients who had at least one functioning allele of HIF1A were compared to those who did not using the Mann Whitney U test for continuous variables and chi-square or the Fischer test for discrete variables. Results: 46 patients had both CMR and whole genome sequencing. Only one HIF1A variant was identified in the cohort and present in 13 patients. There were no significant differences in demographics, surgical variables, right or left ventricular volumes or function between patients with and without the variant. Despite a trend towards a lower age at the time of CMR (11.3 vs 13.7 years; p = 0.07), patients with HIF1A variants had higher native T1 values (1094 vs. 1050; p = 0.027) in the right ventricular outflow tract myocardium, reflecting increased diffuse interstitial ventricular fibrosis in them. Conclusion: Hypoxia-inducible factor is associated with imaging markers of increased diffuse right ventricular fibrosis late after repair of tetralogy of Fallot.